Evaluation of the character of structural and functional changes in cerebral vessels in patients with ischemic cerebrovascular diseases on the background of multifocal lesions. - Rosits'ka, O. A. (Medicni Perspektivi, 2018)
The hemodynamic consequences of brain damage depend on the state of the autoregulation system of the cerebral circulation, on the severity, prevalence and rate of progression of the atherosclerotic process (one or more basins), changes in the vascular wall, and the features of the anatomical structure of the cerebral vascular system. Most registries cannot determine the cause of stroke in 25-40% of patients - the so-called cryptogenic strokes. Therefore, the question of underestimation of such disorders as tortuosity, extravasal compression, anomaly of development of not only internal carotid arteries, but also vertebral and subclavian arteries in the diagnosis of the effect on the course of cerebral ischemia is raised. In high-risk groups, the effect of pathology in the carotid arteries on the course of cerebral vascular disease is more often compared with the data of similar changes in extracranial vertebral arteries. In the general group of patients with multifocal lesion of the vessels (MFLV), tortuosity of blood vessels were found in the basins of the internal carotid artery (ICA) and vertebral artery (VA), and the frequency of deformations of the vessels of the vertebrobasilar basin predominated over the deformations in the carotid basin. Atherosclerotic lesions of the vessels of the BA (basilar artery) and VA pools were less frequent than the carotid, but more pronounced. Atherosclerotic lesions of the subclavian artery (Left subclavian artery) are significantly more frequent in the group of patients with vascular lesions of the heart, brain and lower limbs. According to the data of the correlation analysis, possible associations of atherosclerotic vascular lesions of the main arteries of the head (MAH) are established, both among them and with other risk factors.